Innovative technologies of personnel development on the example of Sberbank Public Joint Stock Company ("Journal "U". Economy. Management. Finance.", 2024)
The article discusses innovative technologies for personnel development used in modern Russian institutions from various fields of activity. The work covers issues related to the development of personnel in various organizations, including state or municipal ones. One of these institutions is a commercial bank with state participation «Sberbank», on the example of which the practical application of these technologies was considered.
Keywords: personnel development; innovative technologies; personnel management; Sberbank PJSC